Avaliação do efeito da sonicação em enzimas na polpa de açaí (Euterpe edulis) - Furtado, Maraysa Rodrigues (2016)
The non-thermal treatments are promising techniques for the processing of food. Ultrasound is a able to minimize changes during processing and storage of food. The application of ultrasonic waves in foods can inactivate enzymes and microorganisms, as well as assist in the extraction of components. Acai is a fruit with high nutritional value and commercial demand, but easily loses some of its original properties due enzymatic reactions. This study aimed to evaluate and compare the sonication techniques, thermosonication and conventional heat treatment for inactivation of peroxidase and polyphenol oxidase and maintenance of physical-chemical properties of acai pulp. Were evaluated, Moisture content, pH, titratable acidity, lipids anthocyanins, phenolic compounds and reducing sugars activity of peroxidase and polyphenol in acai pulp treated and not treated with ultrasound and heat treatment. For thermosonication temperatures used were 20, 30, 40, 50, 60 ° C for 10 minutes. It was observed that the thermosonication and heat treatment were able to maintain the characteristics of color, pH, water content, lipid, titratable acidity and anthocyanins. Application of treatment with ultrasound at 20 ° C in acai pulp was obtained behavior similar to the heat treatment in the peroxidase activity. While the nectar, none of the treatments showed statistical significance when compared to the control sample. Treatment with ultrasound is promising only if the parameters that interfere with the efficiency of propagation of sound waves, such as soluble solids content and concentration of the components are reduced.